Synthesis and Elastic Characterization of Zinc Oxide Nanowires. (27th February 2008) - Manoharan, M. P.; Desai, A. V.; Neely, G.; Haque, M. A.
Abstract : Zinc oxide nanowires, nanobelts, and nanoneedles were synthesized using the vapor-liquid-solid technique. Young's modulus of the nanowires was measured by performing cantilever bending experiments on individual nanowires in situ inside a scanning electron microscope. The nanowires tested had diameters in the range of 200–750 nm. The average Young's modulus, measured to be 40 GPa, is about 30% of that reported at the bulk scale. The experimental results are discussed in light of the pronounced electromechanical coupling due to the piezoelectric nature of the material.